Literature on Police Reforms in the Nordic Countries - Rolf Granér (Nordisk Politiforskning)
Abstract Several European countries, like the Netherlands, England, Wales and Scotland have implemented or are undergoing major structural changes in order to centralize their police organizations. (Fyfe, Terpstra & Tops, eds. 2013) This goes for the Scandinavian countries as well. As an extra twist, this centralization is presented as decentralization reforms. The purpose of this literature review of the Scandinavian police reforms is to present the studies done so far of these reforms. This with a special address to the non-Scandinavian readers. The presentation is limited to studies of the reform from 2005 and onwards. Most of the monographs are written in Scandinavian languages. Books in English are limited to Degnegaards doctoral dissertation on the Danish police reform. However, four of the authors of the monographs have also presented articles on the studied reforms (Haraholma & Houtsonen 2013; Holmberg 2014; Holmberg & Balwig 2013; Johannesen 2015; Wennström 2013). A general discussion on the Norwegian reform is also found in Christenson et al. (2016). There are also articles in English of more specific studies like Haake et al. (2015) and Vuorensyrjä (2014). The studies presented are of different character. First there are university and empirically based studies, such as Balvig, Holmberg and Nielsen’s (2011) extensive empirical survey of the Danish reform; Degnegaards (2010) dissertation which covers the same reform, from a management perspective; Haraholma’s (2011) evaluation of the Finnish reform, here presented through an article in Fyfe et al. (2013), and Renå’s (2016) survey report from Norway about police employees’ and managers’ attitudes to Norwegian police reform. More specific studies are Vuorensyrjä’s (ibid.) study of changes in organizational and occupational stress in the Finnish police force during the police reform years, and Haake et al. (ibid) on expectations on police leaders during major organizational change pressures. Second, with an empirical base, there are evaluations conducted by a government mandate, such as reports from the Swedish Agency for Public Management (Statskontoret 2016) and from the Norwegian Agency for Public Management and eGovernment (Direktoratet for forvaltning og IKT (Difi) 2017). Third, there are three books which are primarily based in organizational theory and police science and which analyze the basic assumptions behind the police reforms, often in a polemic and popular way. This goes for Wennström’s (2014) and Björk’s (2016) analyses of the background to the Swedish reform, and Johannessen (2015), who examines the development of the Norwegian police.